The Relationship of Sleep Quality with Blood Sugar Levels of Type-2 Diabetes Mellitus Clients - Ridwana, Feni; Agustina, Hana Rizmadewi; Nursiswati, Nursiswati (Jurnal Keperawatan Silampari, 2024)
This study aims to determine the relationship between sleep quality and blood sugar levels in patients with type 2 diabetes mellitus. This research method uses a narrative review with PRISMA guidelines. The databases used are PubMeD, CINAHL, and Garuda Portal, with inclusion criteria being randomized controlled trials (RCT), quasi experiments, cohort studies, cross-sectional studies, published in 2012-2022, full text, and articles in Indonesian and English. The keywords used are Diabetes mellitus AND Sleep quality AND blood glucose and the Garuda Portal database uses the keywords Diabetes mellitus AND sleep quality AND blood sugar levels. The results of the study obtained 12 articles that met the criteria, with each article discussing the relationship between sleep quality and blood sugar levels in patients with type 2 diabetes mellitus. The largest number of respondents was 3,249 respondents and the smallest number of respondents was 32 respondents. A total of 12 articles, 6 articles from Indonesia and 1 article each from China, Taiwan, Iran, Korea, Pakistan and Japan. Conclusion, there is a significant relationship between sleep quality and blood sugar levels in patients with type 2 diabetes mellitus. The relationship between sleep quality and blood sugar levels is that the worse the sleep quality, the higher the blood sugar levels. Keywords: Diabetes Mellitus, Blood Glucose, Sleep Quality